Effectiveness of Know-Want-Learned Learning Strategies on Improving Comprehension in Deaf Students - Alya Jilan Rizqita; Budi Susetyo (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of the Know-Want-Learned strategy for improving the reading comprehension skills of deaf students. This study used a pre-experimental method with a one-group-pretest-posttest design. The sample in this study were 6 deaf students in class VI at SLB – X Bandung City. Data collection was carried out by providing reading comprehension ability test instruments that had been validated by experts and reliability tests on deaf students. The research data analysis technique was processed using nonparametric statistics, tested with the Wilcoxon test. The results of this study prove that the Know-Want-Learned strategy is effective in increasing the reading comprehension skills of deaf students in class VI at SLB – X Bandung City. This effectiveness is evidenced by an increase in reading comprehension skills for class VI deaf students. With indicators of reading comprehension including the ability to understand words or sentences in the text, the ability to relate knowledge and experience in the text and the ability to understand the content in the text.